Reimagining Rural Empowerment: Evaluating the Parish Development Model’s Role in Inclusive and Sustainable Coffee Farming in Uganda - Lumu Emmanuel Roy, Muyingo A; Brenda, Nabachwa B; Faith Mugisha, Ahabyoona C (INTI International University, 2025)
This study evaluates the Parish Development Model (PDM) as a decentralized rural development initiative aimed at enhancing the economic empowerment of coffee smallholder farmers in Hoima District, Uganda. Using a convergent mixed-methods approach, the research integrates Sen’s Capability Approach, Resilience Theory, and Social Capital Theory to examine three dimensions: institutional support, resource capacity building, and community engagement. Quantitative data were collected from 278 farmers through stratified random sampling, while qualitative insights were obtained from 12 key informant interviews and 8 focus group discussions. Findings indicate that while PDM has improved coffee yields by 37% among beneficiaries and strengthened trust in SACCOs with transformational leadership, significant barriers persist, including elite capture, gender-based land tenure disparities, and low uptake of climate-smart practices. Policy recommendations include community-vetted beneficiary selection, gender-responsive governance measures, and climate-resilient financing. The results offer lessons for scalable decentralized development models applicable in ASEAN and other Global South contexts.